UPAYA MENINGKATKAN AKTIVITAS BELAJAR IPAS MELALUI MODEL PROBLEM BASED LEARNING PADA MATERI PERUBAHAN WUJUD BENDA DI KELAS IV SDN KEDOYA SELATAN 04 PAGI - Yolanda, Nabilla; Syofyan, Harlinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by low student participation, lack of motivation, and suboptimal learning outcomes. Many students tend to be passive and less courageous in contributing to class discussions, which makes the learning atmosphere less interactive. The purpose of this study is to determine the application of the Problem Based Learning (PBL) model can improve student learning activities in science on the material of changes in the state of matter in grade IV. The Problem Based Learning (PBL) learning model is a learning model to improve students' problem-solving, collaboration, and critical thinking skills. This research was conducted in two cycles, each cycle includingplanning, implementation, observation, and reflection activities. The subjects of this study were 28 fourth-grade students of SDN Kedoya Selatan 04 Pagi. The data analysis techniques used were qualitative and quantitative data analysis techniques. The results of the study indicate that the Problem Based Learning (PBL) learning model can improve the learning activities of fourth-grade students of SDN Kedoya Selatan 04 Pagi on the material of changes in the state of matter. This can be seen from cycle 1 meeting 1 based on student learning activities with a percentage of 52% with a fairly good category, in cycle 1 meeting 2, there was an increase in student learning activities with a percentage of 61% with a good category. Then cycle 2 at meeting 1 student learning activities with a percentage of 82% with a very good category and in cycle 2 meeting 2, there was also an increase in student learning activities with a percentage of 87% with a very good category. From the 2 cycles that have been implemented, it turns out that the expected action intervention results have been achieved, namely achieving the Minimum Completion Criteria (KKM) of 85% exceeding the KKM.